Characteristics of Newborns Born to SARS-CoV-2-Positive Mothers: A Retrospective Cohort Study - Farghaly, Mohsen A.A.; Kupferman, Fernanda; Castillo, Fiorella; Kim, Roger M. (American Journal of Perinatology, 2020)
Objective The novel virus known as severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) has led to a terrifying pandemic. The range of illness severity among children is variable. This study aims to assess the characteristics of newborns born to SARS-CoV-2-positive women compared with those mothers who tested negative.Study Design This was a retrospective cohort study performed at Brookdale Hospital Medical Center in New York City from March to May 2020. Electronic medical records of mother–baby dyads were reviewed.Results Seventy-nine mothers tested for SARS-CoV-2 were included, out of which 18.98% of mothers tested SARS-CoV-2 positive. We found a significant association between symptoms and SARS-CoV-2 status. We observed a significant association between newborns of SARS-CoV-2 positive and SARS-CoV-2 negative mothers regarding skin-to-skin contact (p < 0.001). Both groups showed significant differences regarding isolation (p < 0.001). Interestingly, regarding SARS-CoV-2 infection in newborns, only one newborn tested SARS-CoV-2 positive and was unstable in the neonatal intensive care unit (NICU). With the multivariable logistic regression model, babies of SARS-CoV-2 positive mothers were three times as likely to have desaturations in comparison to newborns from negative mothers. Also, newborns of SARS-CoV-2-positive mothers were four times more likely to have poor feeding, compared with newborns of SARS-CoV-2-negative mothers. Finally, babies of SARS-CoV-2-positive mothers were ten times more likely to be symptomatic at the 2-week follow-up.Conclusion SARS-CoV-2 has caused major morbidity and mortality worldwide. Neonates born to mothers with confirmed or suspected SARS-CoV-2 are most of the time asymptomatic. However, neonatal critical illness due to SARS-CoV-2 is still a possibility; thus, isolation precautions (such as avoiding skin-to-skin contact and direct breastfeeding) and vertical transmission should be studied thoroughly. In addition, testing these newborns by nasopharyngeal swab at least at 24 hours after birth and monitoring them for the development of symptoms for 14 days after birth is needed.Key Points
Keywords: COVID-19; newborn; NICU; pandemic; SARS-CoV-2